2010
DOI: 10.1104/pp.110.159152
|View full text |Cite
|
Sign up to set email alerts
|

A GlutathioneS-Transferase Regulated by Light and Hormones Participates in the Modulation of Arabidopsis Seedling Development

Abstract: Glutathione S-transferases (GSTs) have been well documented to be involved in diverse aspects of biotic and abiotic stresses, especially detoxification processes. Whether they regulate plant development remains unclear. Here, we report on our isolation by reverse transcription-polymerase chain reaction of a plant GST, AtGSTU17, from Arabidopsis (Arabidopsis thaliana) and demonstrate that its expression is regulated by multiple photoreceptors, especially phytochrome A (phyA) under all light conditions. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 52 publications
3
99
0
1
Order By: Relevance
“…3). Glutathione modulates development of Arabidopsis plants 24 which is similar to the results by Jahan et al 11 who showed that a deficient GSH content controls leaf development as well as plant growth of ch1-1 mutant Arabidopsis plants. These results agree with our study.…”
Section: Discussionsupporting
confidence: 77%
“…3). Glutathione modulates development of Arabidopsis plants 24 which is similar to the results by Jahan et al 11 who showed that a deficient GSH content controls leaf development as well as plant growth of ch1-1 mutant Arabidopsis plants. These results agree with our study.…”
Section: Discussionsupporting
confidence: 77%
“…GSH and glutaredoxins are concerned with detoxification of ROS, but they also transmit redox signals under drought stress (Meyer 2008). The GSH pools in the Arabidopsis atgstu17 mutant were 35% higher compared with wild-type plants (Jiang et al 2010). Application of exogenous betaine and proline application improved GSH level and maintained high activities of GST and Gly I, thereby protecting lentil plants from oxidative damage and toxic effects of MG (Molla et al 2014).…”
Section: Droughtmentioning
confidence: 99%
“…Interestingly, the association of phyA with the NAC019 promoter mediates the transcriptional regulation of NAC019 in response to both FR and ABA (Figures 6 and 8). As NAC019 is a transcription factor, it is conceivable that At GSTU17, a GST that participates in ABA-mediated inhibition of root elongation under white light (Jiang et al, 2010), is subsequently regulated by NAC019 under FR. It is likely that more ABA-responsive intermediates in addition to NAC019 are also involved in FR-modulated root elongation, since NAC019 has multiple functionally redundant homologs, such as NAC072 and NAC055 (Tran et al, 2004).…”
Section: A Broad Range Of Transcription Factors Act Downstream Of Phyamentioning
confidence: 99%
“…Moreover, abscisic acid (ABA) signaling interferes with phyA-dependent seed germination (Lee et al, 2012). On the other hand, phyA synergistically coordinates with ABA to inhibit root elongation under white light (Jiang et al, 2010). Yet, the mechanism by which phyA influences the expression of ABA-responsive genes and collaborates with ABA responses under FR awaits further investigation.…”
Section: Introductionmentioning
confidence: 99%